1998
DOI: 10.1038/sj.onc.1201719
|View full text |Cite
|
Sign up to set email alerts
|

Increased cell growth and tumorigenicity in human prostate LNCaP cells by overexpression to cyclin D1

Abstract: Deregulated expression of cyclin D1 has been found in several types of human tumors. In order to investigate factors involved in human prostate cancer progression, we studied the e ects of cyclin D1 overexpression on human prostate cancer cell proliferation and tumorigenicity by transfecting LNCaP cells with a retroviral vector containing human cyclin D1 cDNA. When compared to the parental and control-vector transfected LNCaP cells, these cyclin D1-transfected cells had more cells in Sphase and lower growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 31 publications
(54 reference statements)
7
51
0
Order By: Relevance
“…Cyclin D1 mRNA levels are increased in both primary prostate cancer samples (Han et al, 1998) and androgenindependent bone metastasis (Drobnjak et al, 2000). Furthermore, increased expression of cyclin D1 in LNCaP enhanced cell growth and tumorigenicity (Chen et al, 1998;Perry et al, 1998). Therefore, inhibition of cyclin D1 may be an interesting molecular target to control tumor proliferation (Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 mRNA levels are increased in both primary prostate cancer samples (Han et al, 1998) and androgenindependent bone metastasis (Drobnjak et al, 2000). Furthermore, increased expression of cyclin D1 in LNCaP enhanced cell growth and tumorigenicity (Chen et al, 1998;Perry et al, 1998). Therefore, inhibition of cyclin D1 may be an interesting molecular target to control tumor proliferation (Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Excess of MMPs stimulates tumour invasion and metastasis (Kugler, 1999;Sato et al, 1992). Cyclin D1 initiates the G1-S phase progression (Chen et al, 1998). Oestrogens are found to induce nuclear localization of Cyclin D1 in endometrial cells, resulting in increased cell proliferation (Tong and Pollard, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1, whose expression is increased in prostate cancer cell lines and clinical tumors, is causally related to tumorigenesis (38). In vivo cyclin D1 overexpression in LNCaP cells yielded faster tumor growth and insensitivity to castration (39). It was also shown that cyclin D1 expression correlates with metastatic spread of prostate cancer to bone (40).…”
Section: Discussionmentioning
confidence: 99%